Position of Kazakhstan in International Trade and Business - Batyrkhanova, Yekaterina; Štěrbová, Ludmila, 1957-; Müller, David, 1979-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
This thesis presents an analysis of trends in world and foreign trade of Kazakhstan. It contains the main indicators characterizing the degree of product and geographic diversification of Kazakhstan's exports and imports. The thesis analyses the features, character and prospects of expansion of foreign economic relations of Kazakhstan, issues of strategic partnership, and trends shaping the model of the regional economy within the boundaries of the Eurasian Economic Space.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses